Reversal of alopecia areata, osteoporosis follow treatment with activation of Tgr5 in mice. Issue 7 (30th July 2021) - Zhou, Xiaohui; Guan, Zhiqiang; Jin, Xiao; Zhao, Jianbin; Chen, Guisheng; Ding, Jicun; Ren, Yile; Zhai, Xiaoxiang; Zhou, Qiyun; Guan, Zhiyuan
Abstract: Background: Alopecia areata is an autoimmune hair loss disease with infiltration of pro-inflammatory cells into hair follicles. The role of Tgr5 in dermatitis has attracted considerable attention. The present study aimed to investigate the effect of Tgr5 in the development of Alopecia areata. Methods: The study utilized a comparison control group design with four groups of wild-type group, wild-type+INT777 group, Tgr5 −/− group, and Tgr5 −/− +INT777 group. The mice were treated with INT777 (30 mg/kg/day) or the carrier solution (DMSO) intraperitoneally for 7 weeks, and the back skin was collected and analyzed by histology and immunohistochemistry staining. The lumbar vertebrae 4 has also been analyzed by DXA and Micro-CT. Results: Tgr5 −/− mice displayed the decreasingly significant in hair area and length, skin thickness, and the ratio of anagen and telogen, collagen, and mast cell number and loss the bone mass than WT group. After treating with INT777, the appearance of alopecia areata and bone microstructure has improved. Immunohistochemistry and qPCR analysis showed that activation of Tgr5 can down-regulate the express of JAK1, STAT3, IL-6, TNF-α, and VEGF. Conclusion: These findings indicate that activation of Tgr5 mediated amelioration of alopecia areata and osteoporosis by down-regulated JAK1-STAT3 signaling pathway.